Resilient cities urban nutrition profile: Peru - Margolies, Amy; Vilca, Jessica Huamán; Pather, Kamara; Olney, Deanna K. (International Food Policy Research Institute, 2024)
Key Messages -Peru has made significant strides in reducing the burden of stunting, but progress has stalled: 8 percent of urban children and 20 percent of rural children are stunted. -Overweight and obesity in women have been highly prevalent for more than a decade, with no signs of improvement; they affected 66 percent of urban and 61 percent of rural women in 2023). The problem also affects school-age children, adolescents, and adult men. -Peru has the third highest urban sugar intake among eight countries in the region, but saturated fat intake is comparatively lower than the regional average (6.5% of total energy compared to 9.7%). Among all adults, consumption of fruits and vegetables is low. -The cost of a healthy diet increased from $3.28 to $4.00 per person per day from 2017 to 2022, and 34% of the total population is unable to afford a healthy diet. -Urban food environment (FE) studies, which mostly focus on Lima, Peru’s capital, should be expanded to other urban areas (e.g., smaller urban areas and Amazonia) and to rural areas where FEs have also started to undergo rapid changes. -Research is needed to better understand how level of urbanicity, region (Amazon/Andean), ethnicity, or settlement type intersect to affect nutrition and diets. -Evidence regarding the success of urban nutrition interventions is inconsistent and there is limited guidance on how nutrition programs can be adapted to urban contexts. -Double-duty actions to address poor diets and the multiple forms of malnutrition that are affecting both urban and rural areas are urgently needed. These should include a redesign of social protection programs to ensure that they focus on healthy foods and meals and address all forms of malnutrition, especially among school-age children and women. -While Peru has nutrition policies that both cover urban dwellers and encourage consumer demand for healthier diets and improved access to food, these programs should be adapted to effectively do double duty in preventing all forms of malnutrition, particularly overweight. -Policy implementation and enforcement must be strengthened to address obesogenic FEs. In addition, accompanying interventions that target children and adolescents and innovations that stimulate consumer demand for healthier and more sustainable diets are needed.